Analisis Proses Pemecahan Masalah Matematika Berdasarkan Kerangka Kerja Mason pada Siswa SMP dengan Kategori Kemampuan Berpikir Kritis Matematis yang Berbeda - Nurhalisa, Tika; Sulistyaningrum, Heny (Jurnal Riset Pembelajaran Matematika, 2024)
Problem-solving ability is an ability that affects the success of learning mathematics. One that affects problem-solving ability is critical thinking ability. Teachers must know the problem-solving process that students have to improve the problem-solving-oriented learning process. The purpose of this qualitative descriptive study was to analyze the mathematical problem-solving process based on the Mason framework for junior high school students with different categories of mathematical critical thinking abilities. The subjects of this study were 4 grade VII E students of SMP Negeri 5 Tuban with high and low mathematical critical thinking skills categories. The instruments used are written test questions for comparison materials with FRISCO indicators, written test questions for comparative materials in the form of HOTS, and interview guidelines. The results of the study will be analyzed descriptively and qualitatively based on the Mason framework. From the results of the study, it can be concluded that: (1) subjects with the category of high critical thinking skills can solve HOTS questions with cognitive levels C4, C5, and C6 correctly and fulfill all Mason's framework, namely the entry, attack, and review stages; (2) subjects with low mathematical critical thinking skills were unable to solve all HOTS questions with cognitive levels of C4, C5, and C6 and only met Mason's framework, namely the entry stage with complete aspects.